BETAINE SUPLEMENTATION TO IMPROVE BROILER PERFORMANCE - Putra, Widihantoro Gunawan; Ardana, Ida Bagus Komang; Suharsono, Hamong (Buletin Veteriner Udayana, 2021)
The poultry industry in Samarinda faces high environmental temperatures with high air temperatures between 20 ° C-34 ° C with an average rainfall per 1980 mm, and the average humidity is 85%. High temperatures can trigger heat stress that can disrupt the broiler's growth, which affects weight loss, increase FCR (feed conversion ratio) value, and decrease IP value (Performance Index). This study aims to determine the effect of giving different doses of betaine through drinking water in improving broiler performance, including weight, FCR and IP. The sample of this study amounted to 1,200 7-day old female broilers and the results were analyzed with statistical analysis of Completely Randomized Design (RAL) with four treatments, the dose used is; P0 (0.0 g/L), P1 (0.5 g/L), P2 (1.0 g/L) dan P3 (2.0 g/L). The result of statistical analysis showed that the addition of betaine had a significant effect (P <0.05) for the best average weight gain on treatment P2 (1.0 g/L) 1.870 ± 0.009 d , the best FCR value at treatment P2 (1.0 g/L) 1.500 ± 0.089 a and the best IP value at treatment P2 (1.0 g/L) 368.333 ± 4.033 d . Betaine could increase weight, optimize FCR and improve IP.